2001
DOI: 10.1101/gad.931401
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 specific acetyltransferases are essential for cell cycle progression

Abstract: Longstanding observations suggest that acetylation and/or amino-terminal tail structure of histones H3 and H4 are critical for eukaryotic cells. For Saccharomyces cerevisiae, loss of a single H4-specific histone acetyltransferase (HAT), Esa1p, results in cell cycle defects and death. In contrast, although several yeast HAT complexes preferentially acetylate histone H3, the catalytic subunits of these complexes are not essential for viability. To resolve the apparent paradox between the significance of H3 versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
191
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(214 citation statements)
references
References 71 publications
(89 reference statements)
21
191
1
1
Order By: Relevance
“…The Esa1 H4 HAT is also essential for yeast cell viability (40,41). The cell cycle delays we observe here upon mutation of H3 Ser 10 and loss of GCN5 are highly reminiscent of those observed in our previous studies (21,34) and those observed by Howe et al (39) upon loss of GCN5 and SAS3. One simple explanation is that the lowered acetylation of Lys 9 that occurs upon Ser 10 mutation becomes critical upon loss of other acetylation events mediated by Gcn5.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The Esa1 H4 HAT is also essential for yeast cell viability (40,41). The cell cycle delays we observe here upon mutation of H3 Ser 10 and loss of GCN5 are highly reminiscent of those observed in our previous studies (21,34) and those observed by Howe et al (39) upon loss of GCN5 and SAS3. One simple explanation is that the lowered acetylation of Lys 9 that occurs upon Ser 10 mutation becomes critical upon loss of other acetylation events mediated by Gcn5.…”
Section: Discussionsupporting
confidence: 73%
“…These studies indicated that a certain threshold of acetylation events is required for normal cell cycle progression. Consistent with this idea, concomitant loss of the genes encoding the Gcn5 and Sas3 H3 HAT activities is lethal in yeast (39). The Esa1 H4 HAT is also essential for yeast cell viability (40,41).…”
Section: Discussionsupporting
confidence: 64%
“…These observations suggest that RSC is not dedicated to cell cycle regulation, although we cannot exclude the possibility that G 2 /M arrest is caused by defective expression of a key G 2 /M-specific gene(s). Interestingly, mutations in histone tails or in other chromatin-modifying activities (e.g., histone acetylases), arrest cells at the G 2 /M transition or slow progression through G 2 /M (Megee et al 1990;Morgan et al 1991;Zhang et al 1998;Clarke et al 1999;Howe et al 2001). …”
Section: Rsc1 and Rsc2 Forms Of The Rsc Complex Associate With Commonmentioning
confidence: 99%
“…As deletion of no single subunit defining modules or complexes recapitulated the synthetic lethality of gas1 gcn5 at 30°, it is likely that Gcn5 catalytic activity itself is the critical factor in the interaction with Gas1, as is observed for the gcn5 sas3 synthetic lethality (Howe et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Gcn5 and Sas3 share nucleosomal H3 targets (reviewed in Lafon et al 2007) and deletion of both GCN5 and SAS3 is synthetically lethal (Howe et al 2001). Further, both Gcn5 and Sas3 are recruited to similar genomic regions (Rosaleny et al 2007).…”
mentioning
confidence: 99%